Role of Economic Dimension for Sustainable Reintegration of Returnee Migrants in Eastern Hill of Nepal - Rai, Mahendra Kumar (Humanities and Social Sciences Journal, 2024)
Reintegration of returnee migrants is one of the most pressing issues of labour sending countries like Nepal. The reintegration of returnee migratns through economic dimension remains significant for succesful and sustainable that contributes for socio-economic and developmental progress of the nation. This study aims to examine the contribution of economic dimension for reintegration of returnee migrants in the study area. This study was carried out in Dhankuta Municipality of Dhankuta District located at eastern hill of Koshi province of Nepal. The survey of 310 returnee migrants was carried out to assess the contribution of economic dimesion for successful reintegration in the origin place. The majority of returnees were from age group 30-34 years with hgih proportion of returnees from Malysia. The likelihood ratio of training recipient is observed 7 times higher for age group 25-34 whereas status of saving and feeling of economic security is found 13 times higher for age group 45-54. The Odds in all three independent variables are observed highest for returnee having education above intermediate level i.e.; Odd ratio 40.60 for training recipient, Odd ratio 6.20 for availability and accessibility of BFIs and Odd ratio 49.79 for status of saving and feeling of security. This shows that economic dimension is crucial for reintegration of returnees. However, special packages of capacity building training and soft loan for start-up fund from local government seem most essential for successful and sustainable reintegration.